Look : how a highly influential magazine helped define mid-twentieth-century America - Yarrow, Andrew L. (Potomac Books, an imprint of the University of Nebraska Press, 2021)
"Andrew L. Yarrow tells the story of Look magazine, one of the greatest mass-circulation publications in American history, and the very different United States in which it existed"--